2022
DOI: 10.1177/14644207221126810
|View full text |Cite
|
Sign up to set email alerts
|

Extremely effective broadband low-frequency sound absorption with inhomogeneous micro-perforated panel (iMPP) backed with spider-web designed cavities

Abstract: Low-frequency wideband noise reduction has posed a significant problem to the scientific and technical communities in recent years. A single layer of a parallel-arranged inhomogeneous micro-perforated panel (iMPP) coupled with spider-web designed cavities is offered as a composite acoustic structure in this paper. Three different spider-web shapes have been designed and studied, i.e. circular, octagonal, and square. By controlling the different inhomogeneous patterns, perforation ratio, the thickness of iMPP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Miniaci et al [7] discovered that metastructures inspired by spiderweb patterns effectively establish band gaps for low frequencies. Furthermore, Rafique et al [8] explored the potential of spiderweb-like structures as rear cavities for micro-perforated non-homogeneous panels, assessing their sound-absorbing efficiency. The increasingly prevalent adoption of 3D printing across industries has presented significant avenues for producing and advancing sound-absorbing materials, particularly acoustic metastructures.…”
Section: Introductionmentioning
confidence: 99%
“…Miniaci et al [7] discovered that metastructures inspired by spiderweb patterns effectively establish band gaps for low frequencies. Furthermore, Rafique et al [8] explored the potential of spiderweb-like structures as rear cavities for micro-perforated non-homogeneous panels, assessing their sound-absorbing efficiency. The increasingly prevalent adoption of 3D printing across industries has presented significant avenues for producing and advancing sound-absorbing materials, particularly acoustic metastructures.…”
Section: Introductionmentioning
confidence: 99%
“…They found that random fiber reinforcement composites showed the maximum SAC due to the untreated fiber reinforcement in the composites. Rafique et al 24 discussed the SA properties of microperforated samples with spider web-shaped cavities using the impedance tube technique. Gokulkumar et al 25 analyzed the SA properties of tea and pineapple leaf fibers composites.…”
Section: Introductionmentioning
confidence: 99%